Appropriate Technology Interventions For The Successful Of Kostratani Program: Agriculture Extension Officers’ Predictions - Anugrah, Iwan Setiajie; Wahyuni, Sri (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2023)
To support the achievement of Kostratani Program, socialization to agriculture extension officers (PPL) had been delivered. Through well understanding on their respective responsibilities, they might able to predict the achievement of the program targets, the factors that support and problem they faced to be overcome to get maximum achievement. To get this information a research had been carried out in three provinces namely, West Java, Lampung, and Central Java in 2021. The respondents were 51, 31, and 34 PPL in BPP from each province. Data were obtained through individual interviews referring to a structured questionnaire on five aspects with 21 indicators. The data ware analyzed based on qualitative analysis and presented descriptively. Results reported by men and women PPL respectively were:1) Socialization was obtained by 67% and 71% ;2) Clarity of the responsibility by 52% and 51%; 3)Their prediction on the Program achievements’ targets was 51% and 50%; 4) Access for on-line applications in supporting data and information was received by 47% and 47% and 5) Access for education (training, comparative studies) and incentives ( monthly honorarium and internet quota) to run the Kostratani Program was only obtained by 21% of men and 24% of women. Concluded, the main intervention needs to be given to PPLs in the BPP Kostratani Program is the access on education and incentives. Meanwhile, in synergy it is still necessary to continue the socialization about Kostratani to increase PPL's understanding of the clarity of tasks or responsibilities to get maximum achievement of Kostratanis’ targets.